The locket : a novel - Evans, Richard Paul. (New York : Simon & Schuster, 1998)
Working at a rest home after caring for his mother during her terminal illness, Michael accepts the deathbed request of an elderly woman to return her cherished locket, given to her by a long-lost love, to her old hometown.
Keywords: Nursing home patients -- Utah -- Fiction; Nursing homes -- Employees -- Fiction; Utah -- Fiction; Love stories